Modal Sosial Penjual Jamu Keliling - Marina Engzelina; Teguh Widodo (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2023)
Social capital is an important thing that includes several elements to achieve a certain goal. The application of elements existing in social capital is necessary in many sectors of human life, one of which is economic sector. The author, in this case, conducted a research related to the social capital in the life cycle of herbal medicine (jamu) peddlers. As known, herbal medicine is used not only in health world but also in beauty world. Seeing the time progress, Other traditional medicines, modern medicine, and science and technology sophistication exist to compete more stringently with the presence of herbal medicine. To anticipate this, the herbal medicine sellers need tips to maintain their herbal medicine business, through social capital. Problem statement in this research is related to the social capital created among the herbal medicine peddlers in Tuah Madani Sub District of Pekanbaru City. The subject of research consisted of 5 herbal medicinal peddlers with the following criteria: having sold herbal medicine for more than 10 years, selling through either carrying their product on their back or riding motor vehicle, native Javanese, and residing in Tuah Madani Sub District neighborhood. The technique of selecting informants used was purposive sampling one. The method used was descriptive qualitative research method. The theory applied in this research was Robert Putnam’s theory stating that there are three elements of social capital: network, trust, and norm. The result of research shows that informants create network, trust, and norm with the sellers of herbal medicine materials in traditional market, sales representative of sachet herbal medicine product, fellow herbal medicine peddlers, buyers, and third parties. The presence of network results in profitable customer relation and the presence of norm can direct the conduct and prevent the dispute in their herbal medicine business activity.